MORPHOLOGICAL MEANS OF PERSUASION IN A PASTORAL MESSAGE OF ANDREY SHEPTYTSKYI - Зелінська, Оксана (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
Modern approaches to the studying of the language are characterized with the awareness of a functional nature of speech, a communicative orientation of all the units and categories of a language system, the understanding of the language as the activity which serves to express a speaker’s intention. In the context of a functional approach to language studies, the research of a speech impact and mechanisms of its realization is a relevant trend in linguistic studios. Ukrainian linguists, based on the outstanding achievements of the researchers, do serious studied of the communicative strategies of a speech impact and tactics of their implementation. A religious discourse, in particular a homiletic one, has been less studied. A denotative communicative feature of a sermon is persuasion – a convincing effect aimed at intellect, emotions and a will of an addressee. To reach persuasion a wide range of linguistic means, namely morphological language resources, is applied. Purpose of the paper is to describe some morphological means of the persuasion realization in Andrey Sheptytskyi’s pastoral messages. Results. Among morphological means of the language, pronouns play an important role in reaching persuasion. Personal, possessive and attributive pronouns are well used in a pragmatic attitude. They ensure the creation of the equality atmosphere with an addressee, facilitate the perception of all the believers as one community or enhance the unequal status of the communication participants, exclude «contradictors» from the communication. Morphological resources of the language add a voluntary nature to a homiletic text. To have an impact on an addressee’s behavior the author uses imperative forms of the verbs. Each personal form of a verb performs different pragmatic functions. Using a verb in the first person plural a preacher identifies himself with believers, sets a close contact with addressees which leads to leveling of a higher position of a speaker as to the addressees. Quite frequently the verbs used in the second person plural in imperative mood function as the persuasion expression in the texts of homiletic epistles. These statements become more imperative, a preacher expresses orders, requests, warnings with their help, he tries to get a steady performance of his instructions. Originality. The originality of the paper consists in the fact that a pragmatic role of pronouns and personal forms of the verbs is described to implement a convincing impact on an addressee in a homiletic discourse based on the material of pastoral messages of the Metropolitan A. Sheptytskyi. Conclusion. A homiletic work, one of its forms is a pastoral message, has some specific communicative peculiarities. The purpose of a sermon is, with help of a verbal impact, to persuade an addressee to change a behavior, to make him live in accordance with Christian morals, to strengthen him in belief or convert to faith. Morphological linguistic resources which the author uses in compliance with a pragmatic instruction facilitate actively the achievement of this goal.